AN ANALYSIS ON ENGLISH TEXTBOOK ENTITLED “LET’S LEARN ENGLISH” FOR THE TENTH GRADER OF SENIOR HIGH SCHOOL BASED ON THE BASIC COMPETENCE OF THE 2013 CURRICULUM (RETAIN, 2020)
There are so many textbooks published to support the teaching and learning English. The teacher uses textbook as a guide to teach English in the classroom. Every textbook must have different characteristic and quality, so that affect the learning process for each student. Due to that condition, not all textbooks are suitable to fulfill the students’ needs and appropriate with the 2013 curriculum in this country. Thus, the textbook really needs to be analyzed and evaluated to improve its quality and values. This research analyzes an English textbook entitled “Let’s Learn English” for the tenth grader based on the 2013 Curriculum. The assessment used is the rubric from BSNP which in line with the core and basic competence. The purpose of this study is to analyze the conformity of the textbook with the core and basic competence of the 2013 curriculum. This research uses a descriptive qualitative approach which consists of more explanation in detail. The data source of this research is an English textbook entitled “Let’s Learn English”. The researcher conforms the materials of textbook to the Core and Basic Competence of the 2013 Curriculum using the rubric assessment form BSNP. The researcher uses document analysis as the method of collecting data. Finally, the researcher concludes that not all the chapters of textbook entitled “Let’s Learn English” are appropriate and fulfill the compatibility with the core and basic competence of 2013 Curriculum. The researcher found that only 62,5% of the materials which fulfilled the core and basic competence of the 2013 curriculum and compatible with the rubric criteria of BSNP. Keyword: English textbook, core and basic competence, 2013 curriculum, rubric assessment